Temperature and ph effects on the treatment of saccharine sorghum broth - Costa, Gustavo Henrique Gravatim [UNESP]; Missima, Jorge Otávio; Teixeira, Vitor [UNESP]; Mutton, Miguel Angelo [UNESP]; Mutton, Márcia Justino Rossini [UNESP] (Centro Universitario de Maringa, 2018)
The effects of different temperatures and pH on the treatment of saccharine sorghum broth are analyzed. Experimental design comprised sub-subplots and the main treatments consisted of different sorghum genotypes (BRS509, CV568 and BRS511); different secondary treatments at different pH (6.0; 6.5; 7.0); tertiary treatments at different temperatures: 65°C, 80°C and 100°C. The chemical and technological characteristics of extracted and clarified broth were assessed. Genotypes BRS 509 and BRS511 had higher amounts of sugar than CV568. Broth at pH 6.0 triggered a lower removal rate of sugars and non-sugars in the broth. The heating of the broth at temperatures lower than 100°C caused flotation of slug and the removal of starch to the detriment of heating at 100°C, when slug sedimentation and non-removal of starch occurred. This may be metabolized by yeast when previously hydrolyzed by amylolytic enzymes. Treatment of broth at pH 6.0 and at 100°C is the most adequate treatment for saccharine sorghum.
Efeito da temperatura e do ph no tratamento do caldo de sorgo sacarino
Keywords: Bioenergy; Simple liming; Sorghum bicolor; Sugar-energy sector